Pemikiran Filosof Yusuf Qordawi Perspektif Ekonomi Islam - Dwi Harjana; Lomba Sultan; Muhammad Saleh Ridwan (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
Yusuf Al-Qardhawi's thoughts have high relevance in dealing with the problems of modern life, especially in the context of the Qur'an as a guide for society and individuals, democracy, Islamic faith, bank interest, Islamic economics, and consumption. However, in-depth studies related to his thoughts are still not systematically integrated in the academic literature, so research is needed to fill this knowledge gap. This research uses descriptive qualitative method to deeply analyze various works and thoughts of Yusuf Al-Qardhawi based on primary and secondary sources. The results showed that Yusuf Al-Qardhawi emphasized the importance of the Qur'an as a comprehensive guide for the life of the people, with a sharia-based approach that rejects bank interest and encourages a just Islamic economic system. In his view on democracy, he integrates Islamic values to support justice and public participation. In addition, his thoughts on consumption emphasize a simple and ethical lifestyle as part of sharia. The implication of this research is to provide an academic and practical foundation in the development of contemporary Islamic studies as well as the preparation of regulations that are relevant to the needs of modern society.